Yearbook of the United Nations 2008 - United Nations (United Nations, 2008)
With its comprehensive coverage of political and security matters, human rights issues, economic and social questions, legal issues, and institutional, administrative and budgetary matters, the Yearbook of the United Nations is the most authoritative reference work available on the activities and concerns of the Organization. Fully indexed, the Yearbook includes the texts of all major General Assembly, Security Council and Economic and Social Council resolutions and decisions. This latest volume, the sixty-second, highlights the attention given by the United Nations in 2008 to conflicts in the Democratic Republic of the Congo, the Georgian province of Abkhazia, and the Sudan, along with the challenges posed by the global food security crisis, severe economic recession, climate change, natural disasters, piracy and terrorism.